Unicorn (and Horse) - Miles, David (David W.); Mengert, Hollie (Library of Congress Cataloginf-in-Publication Data : Familius LLC, 2018)
Everyone loves Unicorn, but next to him, Horse feels plain, grumpy, and unloved ... until Unicorn is kidnapped, and only Horse can save him.
Keywords: Horses -- Juvenile fiction; Unicorns -- Juvenile fiction; Friendship -- Juvenile fiction; Jealousy -- Juvenile fiction; Horses -- Fiction; Unicorns -- Fiction; Jealousy -- Fiction; Friendship -- Fiction; JUVENILE FICTION -- Animals -- Dragons, Unicorns & Mythical; JUVENILE FICTION -- Animals -- Horses; Friendship; Horses; Jealousy; Unicorns; Picture books; Fantasy fiction; Fantasy fiction; Fiction; Juvenile works; Picture books; Fantasy fiction; Picture books